Diet with Concentrate Containing Durio zibethinus Murr Seed Meal: Nutrient Contents, Fatty Acid Profiles, In Vitro Characteristics, and Nutrient Digestibility in Dairy Cows - Endang Sulistyowati; Irma Badarina; Sigit Mujiharjo; Tamrin Simbolon; Idop Rohani Purba (Faculty of Animal Science, Universitas Gadjah Mada, 2019)
This research was to evaluate concentrate diet containing Durio zibethinus seed meal (DSM) on nutrient contents, fatty acid profiles, in vitro characteristics, and nutrients digestibility in dairy cows. The experiment was arranged in Latin Square 4 x 4 design with 4 lactating dairy cows in 4 periods in 2 weeks for each period. The treatments were diets with concentrate containing ratios of rice bran and DSM, DC 35/12.5 (35% of Rice bran+ 12.5% of DSM), DC 27.5/20 (27.5% of Rice bran+ 20% of DSM), DC 20/27.5 (20% of Rice bran+ 27.5% of DSM) and DC 12.5/35 (12.5% of Rice bran+ 35% of DSM). Data were analyzed using analysis of variance (Anova), if any significant difference among treatment means were found, will be further analyzed using Duncan Multiple Range Test (DMRT). Results showed that 20% of DSM supplemented in concentrate improved nutrient contents of crude protein, ether extract, medium chain fatty acid (MCFA), long chain fatty acid (LCFA), polyunsaturated fatty acid (PUFA), unsaturated fatty acid (UFA), and n6/n3. In vitro dry matter digestibility, organic matter digestibility, N-NH3, and total VFA were high in concentrate containing 35% DSM. However, in vivo digestibility evaluation showed nutrient intakes were no differences among treatments. Nutrient digestibility were found higher in diet with concentrate containing 27.5% of DSM. There were three different optimal levels could be suggested, 20% of DSM (for nutrient and fatty acid content), 27.5% of DSM (for nutrient digestibility), and 35% of DSM (for in vitro characteristics). Supported by previous milk production, it was concluded that the 27.5% of DSM was suggested to be applied in concentrate for dairy cows.